Feeding intake and cost for recovering ovarian activity in crossbreed dairy cows undergoing anestrus - Ferreira, Ademir de Moraes; Torres, Ciro Alexandre Alves; Sá, Wanderlei Ferreira de; Viana, João Henrique Moreira (Pesquisa Agropecuaria Brasileira, 1999)
This study was carried out to verify feeding intake and cost for recovering ovarian activity in crossbreed cows (Holstein x Zebu). Eighteen non-pregnant cows were used, exhibiting poor body condition, showing cessation of estrus cycle, normal size ovary and no palpated follicles. Twelve animals were maintained indoors and fed to gain weight until recovering ovarian cyclicity. The other six cows, the control group, were fed to maintain weight and to remain in anestrus during the study. Ovarian activity was evaluated by the level of serum progesterone (sampled each seven days), by retal examination of ovaries each twelve days and visual estrus checked three times a day. The recovered ovarian activity required an average feed consumption of 722.4 kg of dry matter, 50.4 kg of crude protein and 402.4 kg of NDT, relative to an average consumption of 2,374.2 kg of silage and 194.1 kg of concentrate. Feeding cost plus milking production cost, estimated to increase the calving interval, were estimated as being similar to 1,364.2 L of milk. The elevated cost to recover anestrus increases the final cost of milk production, due to the high incidence of anestrus in the Brazilian herds.